Impacts of Microgravity Analogs to Spaceflight on Cerebral Autoregulation - Kermorgant, Marc; Nasr, Nathalie; Czosnyka, Marek; Arvanitis, Dina N.; Hélissen, Ophélie; Senard, Jean-Michel; Pavy-Le Traon, Anne (Frontiers in Physiology, 2020)
It is well known that exposure to microgravity in astronauts leads to a plethora physiological responses such as headward fluid shift, body unloading, or cardiovascular deconditioning. However, when astronauts come back to Earth, some of them encounter problems related to orthostatic intolerance. An impaired cerebral autoregulation (CA), which could be compromised by the effects of microgravity, has been proposed as one of the main mechanisms responsible for orthostatic intolerance. CA is a homeostatic mechanism that allows to maintain cerebral blood flow for any variations in cerebral perfusion pressure by adapting the vascular tone and cerebral vessel diameter. The ground-based models of microgravity are useful tools for determining the gravitational impact of spaceflight on human body. However, little is known about the impact of microgravity on CA. Here, we review the fundamental principles and the different mechanisms involved in CA. We also consider the different approaches in order to assess CA. Finally, we will focus on the effects of short- and long-term spaceflight on CA and compare these findings with two specific analogs to microgravity: head-down bed rest and dry immersion.